Reverse-Phase HPLC Method for the Estimation of Ornidazole in Human Plasma - Krishnaiah, Y.S.R.; Indira Muzib, Y.; Bhaskar, P.; Srinivasa Rao, G. (Asian Journal of Chemistry, 2010)
A high-performance liquid chromatographic method was developed for the estimation of omidazole in human plasma. Varying amounts of ornidazole drug solution (10 to 800 ng) and 5 mL of ethyl acetate were added to blank human plasma (0.5 mL). The mixture was vortexed for five minutes and centrifuged at 3,000 rpm for 10 min and organic layer was separated and dried under vacuum evaporation .The residue is reconstituted with 0.3 mL of methanol. Twenty microliters of this solution was injected into a reverse phase C-18 column using a mobile phase consisting of methanol and triply distilled water (consisting of 0.4% triethylamine and pH adjusted to 3.6 with 5% orthophosphoric acid) in the ratio of 50 : 50 v/v and the eluents were monitored at 254 nm. The method was statistically validated for its linearity, precision and accuracy. The intra- and inter-day variation was found to be less than 2% indicating that the method is highly precise. Due to its simplicity, sensitivity, high precision and accuracy, the proposed HPLC method may be used for estimation of ornidazole in plasma.